Generation of pralatrexate resistant T‐cell lymphoma lines reveals two patterns of acquired drug resistance that is overcome with epigenetic modifiers. Issue 11 (30th July 2020) - Scotto, Luigi; Kinahan, Cristina; Casadei, Beatrice; Mangone, Michael; Douglass, Eugene; Murty, Vundavalli V.; Marchi, Enrica; Ma, Helen; George, Changchun; Montanari, Francesca; Califano, Andrea; O'Connor, Owen A.
Abstract: While pralatrexate (PDX) has been successfully developed for the treatment of T‐cell lymphoma, the mechanistic basis for its T‐cell selectivity and acquired resistance remains elusive. In an effort to potentially identify synergistic combinations that might circumnavigate or delay acquired PDX resistance, we generated resistant cells lines over a broad concentration range. PDX‐resistant cell lines H9‐12 and H9‐200 were developed, each exhibiting an IC50 of 35 and over 1000 nM, respectively. These lines were established in vitro from parental H9 cells. Expression analysis of the proteins known to be important determinants of antifolate pharmacology revealed increase expression of dihydrofolate reductase (DHFR) due to gene amplification, and reduced folate carrier1 downregulation, as the putative mechanisms of resistance in H9‐12 and H9‐200 cells. Cross resistance was only seen with methotrexate but not with romidepsin, azacitidine (AZA), decitabine, gemcitabine, doxorubicin, or bortezomib. Resistance to PDX was reversed by pretreatment with hypomethylating agents in a concentration‐dependent fashion. Comparison of gene expression profiles of parental and resistant cell lines confirmed markedly different patterns of gene expression, and identified the dual specificity phosphatase four (DUSP4) as one of the molecular target of PDX activity. Reduced STAT5 phosphorylation following exposure to PDX was observed in the H9 but not in the H9‐12 and H9‐200 cells. These data suggest that combination with hypomethylating agents could be potent, and that DUSP4 and STAT5 could represent putative biomarkers of PDX activity.